2010
DOI: 10.1007/s12012-010-9063-1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Saffron Consumption on Biochemical and Histopathological Heart Indices of Rats with Myocardial Infarction

Abstract: This study was designed to assess the effects of saffron (Crocus sativus) on rats' heart with isoproterenol-induced myocardial injury. Animals were divided randomly into four groups: vehicle-control group (CTL); ISO group, administrated with Isoproterenol 85 mg/kg s.c.; saffron group; and finally combined Saffron + ISO group. Basal and final serum levels of heart troponin I, heart tissue antioxidants and histopathological indices were assessed in all groups. Isoproterenol administration significantly increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 18 publications
0
37
0
Order By: Relevance
“…Existing documents show the antioxidant properties of saffron (Asdaq & Inamdar, 2010;Hosseinzadeh et al, 2005). In a previous study, we demonstrated that pretreatment with saffron through augmentation of antioxidant levels decreased the isoproterenolinduced myocardial damage (Joukar et al, 2010). Therefore, a part of the anti-arrhythmic effects of saffron may be induced by its antioxidant features and stabilizing the redox balances in stressful condition.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Existing documents show the antioxidant properties of saffron (Asdaq & Inamdar, 2010;Hosseinzadeh et al, 2005). In a previous study, we demonstrated that pretreatment with saffron through augmentation of antioxidant levels decreased the isoproterenolinduced myocardial damage (Joukar et al, 2010). Therefore, a part of the anti-arrhythmic effects of saffron may be induced by its antioxidant features and stabilizing the redox balances in stressful condition.…”
Section: Discussionmentioning
confidence: 85%
“…Avicenna, the great Iranian physician (980-1037 A.D.), advised the use of saffron for the treatment of heart palpitations (Chishti, 1991). The cardioprotective effect of saffron and one of its constituents, crocin, in a stressful condition following the injection of high dose of isoproterenol has been confirmed in recent studies (Goyal et al, 2010;Joukar et al, 2010;Sachdeva et al, 2010). In addition, the attenuation effect of saffron on ischemicreperfusion injury of skeletal muscle (Hosseinzadeh et al, 2009), kidney (Hosseinzadeh et al, 2005) and ischemic brain tissue injury (Vakili et al, 2011) is reported.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…[49] 40 adult patients with mild to moderate depression (Hamilton Rating Scale: [18][19][20][21][22][23][24][25] were randomized to C. sativus 15-mg bid versus fluoxetine 10-mg bid.…”
Section: Depressionmentioning
confidence: 99%
“…[1,3,[7][8][9][10][11][12][13][14] In parallel, the possible uses of saffron and its active constituents lead to an increasing number of research studies, some of which have drawn some very useful and intriguing results of active ingredients of saffron, especially against malignancies, cardiovascular and Alzheimer's disease. [15][16][17][18][19][20][21][22] In this minireview, we aim to summarize and critically address previous and current evidence regarding the biological/ pharmacological activities of saffron and its active ingredients and their possible therapeutic uses. The history and structural features of saffron constituents are given in the first part of the review, followed by a comprehensive and critical presentation of the published preclinical and clinical studies and review papers on the pharmacology and potential therapeutic applications of saffron and its main active components.…”
Section: Introductionmentioning
confidence: 99%